Diagnostic Accuracy of Magnetic Resonance Imaging in Endometrial Cancer. Issue 6 (1st July 2012) - McComiskey, Mark H.; McCluggage, W. Glenn; Grey, Arthur; Harley, Ian; Dobbs, Stephen; Nagar, Hans A.
Abstract : Objectives: The objectives of this study were to investigate the accuracy of magnetic resonance imaging (MRI) in predicting the depth of myometrial invasion in the preoperative assessment of women with endometrial cancer and to quantify the impact of MRI as an adjunct to predicting patients requiring full surgical staging. Methods: This was a diagnostic accuracy study of prospective cases in conjunction with STARD guidelines using collected data from a tumor board within a cancer network. Consecutive series of all endometrial cancers in Northern Ireland over a 21-month period was discussed at the Gynaecological Oncology Multidisciplinary Team/tumor board meeting. This study concerns 183 women who met all the inclusion criteria. Main outcome measure was the correlation between the depth of myometrial invasion suggested by preoperative MRI study and the subsequent histopathological findings following examination of the hysterectomy specimen. Secondary end point was how MRI changed management of women who required surgery to be performed at a central cancer center. Results: For the detection of outer-half myometrial invasion, overall sensitivity of MRI was 0.73 (95% confidence interval [CI], 0.59–0.83), and specificity was 0.83 (95% CI, 0.76–0.89). The positive predictive value was 0.63 (95% CI, 0.50–0.74), and negative predictive value was 0.89 (95% CI, 0.82–0.93). Positive likelihood ratio was 4.35 (95% CI, 2.87–6.61), and negative likelihood ratio was 0.33 (95% CI, 0.21–0.52). Magnetic resonance imaging improved the sensitivity and negative predictive value of endometrial biopsy alone in predicting women with endometrial cancer who require full surgical staging (0.73 vs 0.65 and 0.80 vs 0.78, respectively). Conclusions: Preoperative pelvic MRI is a moderately sensitive and specific method of identifying invasion to the outer half of myometrium in endometrial cancer. Addition of MRI to preoperative assessment leads to improved preoperative assessment, triage, and treatment.